Design and Evaluation of a Human Microglia Model: Drug Delivery and the Inhibitory Impact of PPARβ Agonist on Inflammation - Aloufi, Rawan (2024)
Neuroinflammation is a hallmark of various neurodegenerative disorders, including Alzheimer's disease, Parkinson's disease, and multiple sclerosis. Microglia and astrocytes, the primary immune cells of the central nervous system (CNS), play a crucial role in the initiation and progression of neuroinflammation. Peroxisome proliferator-activated receptors (PPARs) and fatty acid-binding proteins (FABPs), which are thought to deliver ligands to PPARs, have emerged as important regulators of glial cell functions and neuroinflammation, making them attractive therapeutic targets for neurodegenerative diseases. However, the specific roles of PPARs in microglia and astrocytes, as well as the impact of age and inflammatory stimuli on their expression and function, remain largely unexplored.